The Influence of Perceived Value of Benefits, Perceived Ease of Technology Use and Customer Trust on Intention to Use Digital Banking Applications - Elizabeth (Jurnal Informasi dan Teknologi, 2023)
The purpose of this study is to ascertain the impact of perceived benefits, ease of use, and trust on interest in utilizing sharia digital banking. The target audience for this study consists of potential users or clients who currently use or plan to use the sharia digital bank application, which is available in five Indonesian cities; the precise number of users is unknown. Probability sampling techniques were used for the sampling process. use basic random sampling to determine the sample. Thus, one hundred participants made up the sample. The findings of surveys filled out by resource persons and interviews provide this main data. Descriptive quantitative data analysis techniques are used in this study. Several more conclusions can be made in light of the data analysis and discussion findings, specifically the following: Perceived convenience has no direct impact on people's desire to use sharia digital banking. Perceived benefits have a direct bearing on people's willingness to use sharia digital banking. People's desire in using sharia digital banking is not directly influenced by trust. Perceived convenience, perceived rewards, and trust all have an impact on people's willingness to use sharia digital banks concurrently.